Congruence between mcy based genetic type and microcystin composition within the populations of toxic Microcystis in a plateau lake, China. Issue 5 (6th May 2013) - Jiang, Yongguang; Yu, Gongliang; Chai, Wenbo; Song, Gaofei; Li, Renhui
Summary: Genetic diversity and differential microcystin contributions within the populations of toxic Microcystis in freshwater ecosystems have not been fully discussed. To illustrate this issue, we sequenced clone libraries of the first adenylation domain of mcyB ( mcyB A1) from Microcystis populations in a plateau lake. Phylogenetic analysis revealed two divergent groups of McyBA1 with two closely related subgroups within Group I. While neutral evolution was indicated on the whole McyBA1 domain, 1–5 recombination breakpoints and several codons under positive or negative selections were found. Significant seasonal changes of McyBA1 diversity were observed. Group I composed the major proportion of the McyBA1 pool throughout the growing season in the whole lake. Group IA and Group II denominated Microcystis strains isolated from this lake were characterized by preference production of microcystin‐RR (62–85%) and microcystin‐LR (> 98%) respectively. We detected the intracellular microcystins in lake water and microcystin‐RR was a main variant (mostly > 50%). In summary, McyBA1 subgroups were dominant within the population of toxic Microcystis and contributed the predominance of microcystin‐RR in the lake. The differences of substrate preference in microcystin biosynthesis among groups were caused by neutral evolution and homologous recombination.